SOCIO-ECONOMIC DITERMINATION IN THE USE OF COMMUNITY HEALTH FACILITIES IN NANGA MBAUR VILLAGE, EAST MANGGARAI REGENCY - Irawan, Ade; Ibrahim (GEMOVE: Journal of Gender, Movement, and Empowerment, 2026)
This study is motivated by the limited utilization of health facilities in rural areas, which is influenced by social, economic, and geographical factors. These limitations contribute to low access and utilization of health services, despite the availability of basic healthcare facilities. The purpose of this study is to analyze the socio-economic determinants of health facility utilization in Nanga Mbaur Village, East Manggarai Regency, and to formulate improvement strategies using a SWOT analysis approach. This research employs a qualitative approach with a descriptive method through direct interviews with community members as respondents. Data were collected through semi-structured interviews covering social aspects such as education level, trust in traditional medicine, and social influence, as well as economic aspects including income level, medical expenses, and transportation costs. Data analysis was conducted using thematic analysis, which was then integrated into a SWOT framework to identify strengths, weaknesses, opportunities, and threats related to health service utilization. The results indicate that social factors shape community perceptions and behaviors, while economic factors act as the primary barriers to accessing health services. In addition, geographical limitations further exacerbate these challenges. Based on the SWOT analysis, strategies categorized into SO, WO, ST, and WT are formulated to improve health facility utilization sustainably. This study highlights the importance of a place-based approach to enhance access and quality of healthcare services in rural communities.